Adaptive interpretation of the law: the congress´ purview. Legitimacy of the separation of powers - Godenzi Alegre, Jorge Luis (2021)
The purpose of this paper is to explain some ideas regarding the infinite academic legal opinions on the separation of powers —which still enjoys enormous consideration and monitoring not only at theoretical but also at practical levels— with the irreplaceable and essential function fulfilled by the Congress of the Republic, the Seat of Sovereignty, when it acts as an oversight body and interpreter of the law..